PALEOCENE/EOCENE TRANSITION IN THE NORTHEASTERN PERI-TETHYS AREA: SOKOLOVSKII KEY SECTION OF THE TURGAYB PASSAGE (KAZAKHSTAN) - Radionova E.P.; Khokhlova I.E.; Beniamovskii V.N.; Shcherbinina E.A.; Iakovleva A.I.; Sadchikova T.A. (My University, 2001)
Lithology, microfossils, and stratigraphy of the uppermost Paleocene - lowermost Eocene predominantly terrigenous and siliceous sediments from the Sokolovskii section located in the Turgay Passage, northern Kazakhstan, were studied. Among the microfossils, calcareous nannofossils, radiolarians, and especially dinocysts proved to be useful for age determinations, correlation with standard zonal schemes, and for paleocological reconstructions. The NP8 (Heliolithus riedelii) nannoplankton Zone, the Acarinina subsphaerica and A. acarinata (lowermost part) planktonic foraminifera Zones, the Petalospyris foveolata regional radiolarian Zone, the Moiseivia uralensis diatom Zone were recognised, as well as four dinocysts zones : the Alisocysta margarita, Apectodinium hyperacanthum, A. augustum, and Wetzeliella meckelfeldensis Zones. Also, two transgressive-regressive cycles are distinguished. They are interrupted by short hiatuses; the upper one corresponds to the boundary between the Apectodinium augustum and Wetzeliella meckelfeldensis dinocyst Zones.
Keywords: Paleocene; Eocene; Cenozoic::Paleogene::Eocene; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Эоцен; Кайнозой::Палеоген::Палеоцен